Crystalline structure of polyamide 12 as revealed by solid-state 13C NMR and synchrotron WAXS and SAXS - Dencheva, Nadya Vasileva (2005)
The crystalline structure of polyamide-12 (PA12) was studied by solidstate 13C nuclear magnetic resonance (NMR) as well as by synchrotron wide- and small-angle X-ray scattering (WAXS and SAXS). Isotropic and oriented PA12 showed different NMR spectra ascribed to c- and c0-crystalline modifications, respectively. On the basis of the position of the first diffraction peak, the isotropic c-form and the oriented c0-form were shown to be with hexagonal crystalline lattice at room temperature. When heated, the two PA12 polymorphs demonstrated different behaviors. Above 140 8C, the isotropic c-PA12 partially transformed into a-modification. No such transition was observed with the oriented c0-PA12 phase even after annealing at temperatures close to melting. A c0–c transition was observed here only after isotropization by melting point. Various structural parameters were extracted from the WAXS and SAXS patterns and analyzed as a function of temperature and orientation: the degree of crystallinity, the d-spacings, the Bragg’s long spacings, the average thicknesses of the crystalline (lc) and amorphous (la) phases, and the linear crystallinity xcl within the lamellar stacks.